SYNTHESIS OF POLYOL ESTERS FOR BIODEGRADABLE DRILLING FLUIDS FROM NON-EDIBLE RESOURCES - Nik Mohamad Kamil, Ruzaimah (Universiti Teknologi PETRONAS, 2012)
Environmental pollution as well as the increasing demand for drilling deeper and into hotter formations has initiated the change of oil based mud (OBM) to synthetic based mud (SBM). OBMs are known to cause environmental, toxicological and ecological disruption to the marine environment. In addition, barite sag in OBMs has also become a major concern in highly deviated and horizontal well. This has necessitated the findings of drilling fluids that performs as well as the conventional OBMs, meet the environmental requirements and solve the barite sag issues associated with OBMs. Synthetic bases fluids, primarily ester, have been researched to meet these targets. The present work is focused on the synthesis of polyol esters as biodegradable baseoil for drilling mud which was conducted via chemical transesterification of jatropha oil methyl ester (JOME) with trimethylolpropane (TMP) and esterification of hexanoic acid (HA) with neopentyl glycol (NPG), using sulfuric acid as the catalyst.